MAKNA DENOTATIF DAN KONOTATIF UANG PANAI’ DALAM TRADISI BUGIS BONE - Hamzah, Nur Afifah; Alfikri Rausen Aditya; Mashud, Mashud (Universitas Hamzanwadi, 2024)
The purpose of this research is to reveral the meaning contained in the tradition of uang panai’ which is always viewed from a negative perspective, but there are positive meanings that can be propagated in the tradition. The research method used is a qualitative description with the type of research namely field research. The theory used is Roland Barthes’ semiotic theory which examines denotation and connotation meanings. The result of this study found that the denotative meaning of uang panai’ in Bugis society has been understood as money given to the bride for shopping purposes at the wedding. There are three connotative meanings, namely as a symbol of social strata, a symbol of binding and as a symbol of respect for women.